Edukasi Membangun Kesadaran Bahaya Berita Hoaks dan Ujaran Kebencian di Media Sosial di Lingkungan Siswa/Siswi SMK Negeri 6 Kota Yogyakarta - Tiffany Setyo Pratiwi; Dzikrina Sukma Amelia; Athiya Zahra Rahmanto; Annisa Nur Sholikah; Cindy Citra Adelia Agustin; Charisya Nizrina Putri; Nadhira Wira Khalisha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The author's dedication carries a very important theme, namely the dangers of hoax news and hate speech on social media. This theme was chosen because fake news has had a negative impact on the nation's generation and hate speech is an action that can damage national unity. So the awareness of the younger generation to wisely use social media and receive information is very crucial. This agenda was held at SMK Negeri 6 Yogyakarta City. The aim of this service activity is to increase awareness of Indonesia's young generation, especially among students, to be wise in using social media. The method of service activities is education through face-to-face socialization at SMK Negeri 6 Yogyakarta City, followed by discussions and questions and answers with activity participants. This service was attended by around 15 students from classes X and XI. This activity runs smoothly and students are very enthusiastic about participating.